Preparation and characterisation of modified reclaimed asphalt using nanoemulsion acrylate terpolymer. Issue 5 (2nd September 2019) - Naser, Abdelrahman Moukhtar; Abd El - Wahab, Hamada; Moustafa El Nady, Mohamed Abd El Fattah; E.A. Mostafa, Abdelzaher; Lin, Long; Sakr, Ahmed Galal
Abstract : Purpose: This paper aims to investigate the best methods of utilisation of reclaimed asphalt pavements (RAP) in Egypt, to determine the effect of using 100% RAP instead of using virgin aggregates and asphalt; investigate the effect of thermoplastic elastomer polymer as asphalt modifier; and also improve the mechanical and physical characteristics and consequently improving the quality of asphalt paving, increasing service life of asphalt-paving and reducing costs. Design/methodology/approach: Nano acrylate terpolymers were prepared with different % (Wt.) of and were characterised by Fourier transforms infrared (FTIR), for molecular weight (Mw), by thermo gravimetric analysis (TGA) and by transmission electron microscopy (TEM). A 4% (Wt.) of the prepared nanoemulsion terpolymer was mixed with virgin asphalt as a polymer modifier, to improve and reuse of the RAP. The modified binder was tested. The tests conducted include penetration, kinematic viscosity, softening point and specific gravity. Application of Marshall mix design types; hot mix asphalt (HMA), warm mix asphalt (WMA) and cold in place recycled (CIR). Four different mix designs used; control mix contained virgin asphalt by HMA, and the other three mix designs were polymermodified asphalt sample by HMA, WMA and CIR. Findings: The research results showed that using 4 Wt.% of the prepared nanoemulsion terpolymer to produce hot mix asphalt (HMA) and warm mix asphalt (WMA) achieved higher stability compared to the control mix and cold in place recycled (CIR). Research limitations/implications: This paper discusses the preparation and the characterisation of nanoemulsion and its application in RAPs to enhance and improve the RAP quality. Practical implications: Nano-acrylate terpolymer can be used as a new polymer to modify asphalt to achieve the required specifications for RAP. Originality/value: According to the most recent surveys, Europe produced 265 tonnes of asphalt for road applications in 2014, while the amount of available RAP was more than 50 tonnes. The use of RAP in new blended mixes reduces the need of neat asphalt, making RAP recycling economically attractive.